An Implementation Of Islamic Human Resource Management On Employee Welfare - Nurul Fitrah; Abd. Wahab; Alim Syariati; Muhammad Ghalib; A. Adi Prabowo (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
This study aims to analyze the implementation of Islamic Human Resource Management on employee welfare within an organization. This issue is important to examine because many companies still focus more on productivity and profit orientation rather than comprehensively considering employee welfare, both materially and spiritually. Previous studies have generally focused on Islamic work ethics and Islamic organizational culture, while studies discussing the relationship between the implementation of Islamic Human Resource Management and employee welfare remain relatively limited. This study employs a qualitative approach using a library research method. Data were collected from scientific journals, books, articles, and various literature sources relevant to the research focus. Data collection techniques were conducted through documentation and literature review, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of values such as trustworthiness (amanah), justice, ihsan, and responsibility in human resource management can improve work motivation, loyalty, job satisfaction, and employee welfare both materially and spiritually. This study emphasizes that Islamic Human Resource Management not only functions to enhance organizational productivity but also creates a harmonious work environment oriented toward collective welfare and benefit. Future studies are recommended to employ empirical approaches in order to analyze the implementation of Islamic Human Resource Management more comprehensively across various organizational sectors.Kata kunci: Employee Welfare, Human Resource Management, Islamic Management, Sharia Management